Review Jurnal : Produksi Biofuel dari Palm Oil dengan Berbagai Metode Proses - Muhammad Wafi; Agus Budianto (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Energy is one of the basic needs of all industrial and household needs in the social sphere. Along with population economic growth, regional development and development from year to year, the need for energy fulfillment in all sectors nationally is also getting bigger. The results of a study by the Department of Energy and Mineral Resources explain that Indonesia's total energy consumption per capita is increasing every year with growth of more than 5%. One type of renewable energy is biodiesel. Biodiesel is a fuel oil (BBM) as one of the supporting capacities of human life which will continue to experience an increase in demand along with the increase in population from year to year. Currently, the need for fuel for people around the world is increasing, while fossil fuel reserves are running low. This situation has resulted in scientists developing alternative energy sources which are expected to be able to overcome the energy crisis in the future. In an effort to find, develop, and extract energy sources, the main factors are energy, economy, and ecology. Making green energy in this study we review the process methods that can be used to make biofuel from Pakm Oil raw materials, process methods include the cracking method, hydrocracking method, In this research, the process method that produces the largest % yield is the hydrocracking process method using a Pd/Al2O3 catalyst of 94%.